Rebel rank and file: labor militancy and revolt from below during the long 1970s - Brenner, Aaron; Brenner, Robert; Winslow, Cal (London, 2010)
"From the mid-1960s to 1981, rank-and-file workers in the United States engaged in a level of sustained militancy not seen since the Great Depression and World War II. Millions participated in one of the largest strike waves in US history. There were 5,716 stoppages in 1970 alone, involving more than 3 million workers. Contract rejections, collective insubordination, sabotage, organized slowdowns, and wildcat strikes were the order of the day. Workers targeted much of their activity at union leaders, forming caucuses to fight for more democratic and combative unions that would forcefully resist the mounting offensive from employers that appeared at the end of the postwar economic boom. It was a remarkable era in the history of US class struggle, one rich in lessons for today's labor movement."